State Financial System in Indonesia: Some Recent Developments - Muhamad Adji Rahardian Utama; Muhammad Reza Maulana; Fadhilah Rizky Aftriani Putri; Fauziah Ramadhani; Setyarini Nur Octaviana (Universitas Negeri Semarang, 2020)
The history of the development of the Indonesian financial system, the system of financial institutions underwent a very fundamental change, especially after entering the era of deregulation, the policy package October 27, 1988 which then continued with the enactment of several laws in the field of finance and banking since 1992, starting from the Banking Act, Act Insurance Act, Pension Fund Act, Capital Market Law, until the Bank Indonesia Law. The consequence of the issuance of this law is the change in the structure of the financial institutions in Indonesia. In addition, from the aspect of regulation and fostering, financial institutions are becoming increasingly clear and strong because they already have legal power, especially in the field of insurance and pension funds, which were previously legally regulated only on financial ministerial decisions. This paper analyzes the latest developments in the country's financial system in Indonesia. This paper aims to provide an overview, study, and compare about the developing financial system in Indonesia with several cases of existing financial systems both domestically and abroad. This paper also uses a comparative model of laws, where these laws relate directly or indirectly to the country's financial system.